Silver nanoparticle-incorporated over-oxidized poly(3,4-ethylenedioxythiophene)-based electrochemical sensor for selective determination of riboflavin - Acikalin, Merve Yalcin; Dokur, Ebrar; Uruc, Selen; Gorduk, Ozge; Sahin, Yucel (SPRINGER HEIDELBERG, 2024)
This study presents the development of a selective sensor for the electrochemical determination of riboflavin. In the first step, electropolymerization of 3,4-ethylenedioxythiophene (EDOT) was carried out on the pencil graphite electrode to prepare the modified electrode (PEDOT/PGE). In the second step, we prepared over-oxidized poly(3,4-ethylene-dioxythiophene) pencil graphite electrode (OOPEDOT/PGE) by chronoamperometry method in pH 7.0 phosphate buffer solution. In the final step, silver nanoparticles were deposited on the OOPEDOT/PGE by chronoamperometry. The sensitivity of the developed AgNp/OOPEDOT/PGE sensor to riboflavin has been improved. Cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), X-ray photoelectron spectroscopy (XPS), and Fourier transform infrared spectroscopy (FTIR) were used to characterize the sensor. The surface morphology of the sensor was examined using field emission scanning electron microscopy (FESEM). The limit of detection (LOD) value was determined to be 0.51 mu mol L-1 and a linear range of 0.8 and 80 mu mol L-1 using differential pulse voltammetry (DPV). The sensor demonstrated excellent resistance to interference from dopamine (DA), glucose (G), uric acid (UA), and lactate (LA). The study investigated the applicability of the constructed sensor to real samples and achieved good recovery values. The results indicate that the modified electrode is suitable for riboflavin determination applications.
Keywords: Riboflavin; Over-oxidation; Silver nanoparticles; Poly(3,4-ethylene-dioxythiophene); Differential pulse voltammetry; CARBON-PASTE ELECTRODE; VOLTAMMETRIC DETERMINATION; FILM ELECTRODE; GRAPHITE; NANOCOMPOSITE; Chemistry; Electrochemistry; Physics